PENGGUNAAN ADJEKTIVA EVALUATIF SEBAGAI CERMINAN SIKAP TOKOH DALAM KARYA SASTRA REMAJA PRADA AND PREJUDICE KARYA MANDY HUBBARD - Ni Ketut Mirahayuni; Susie Chrismalia Garnida (Universitas 17 Agustus 1945 Surabaya, 2018)
Abstract. Studies on young adult literature has been flourised since late 20th century and early 21st century and have been interested in identifying defining characteristics of those literary works aimed for young or teen readers. Those studies have focused on the themes, conflicts and characters reflecting the interests of young readers in their search for self identity, adventures, dreams and life problems (Brown and Stephens, 1995; Tri Pramesti, 2016). Other studies examines the language features in young adult literature (Bushman and Haas, 2002; Tri Pramesti, 2015) and language style (Dwi Noverini Djenar, 2008). This article reports a study on the use of evaluative adjectives, a specific language aspect in young adult literature that seems to be employed by the author to express characters’ evaluation toward self and others. The study is conducted within the theoretical framework of systemic functional linguistics analysis of appraisal, particularly the aspects of affect whose realisations involves the use of evaluative adjectives expressing the senses of happiness, security and satisfaction (Halliday and Matthiessen, 2014; Martin and White, 2005). The data were 388 lexical items collected from Mandy Hubbard’s Prada and Prejudice, focusing on the main character’s evaluation of herself and other characters in the novel. The result of the study shows that Prada and Prejudice employs a variety of evaluative adjectives expressing the main character’s evaluation that are related to the sense of happiness, security and satisfaction. This study contributes to better understanding some aspects of language style in literature aiming at young readerships. Keywords: young adult literature, evaluative adjectives, Prada and Prejudice